STRATEGI INDIA EKSPOR OBAT OBATAN KE INDONESIA 2013-2016 - Aulia, Muhamad; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is a economic political study which describes the strategy India to export their pharmacy to Indonesia. This study interesting because describe about drugs from India. India is the third largest country in the production of generic drugs. India can do that after they make some revolusionery in intellectual property law India This is qualitative research which used descriptive methods, and collecting datas from some resources like books, journals, official publications and relevant websites. This paper used the mercantilism perspective and comparative advantage Theory from David Ricardo. The object in this research is India main actor in International Relations. The result of this research shows that strategy India make some revolutionary on their law about intellectual property rights. India make amendment about patent regulation. India also invite Indonesia to conference about traditional medicine. This conference to promote generic drugs from India and make some trade agreement with Indonesia.   Keywords: Straregy, Intellectual Property Rights, Economic Politic, Patent